2015
DOI: 10.1021/acs.nanolett.5b00737
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Resolved Structural and Chemical Investigation of Single MXene Sheets

Abstract: The properties of two dimensional (2D) materials depend strongly on the chemical and electrochemical activity of their surfaces. MXene, one of the most recent additions to 2D materials, shows great promise as an energy storage material. In the present investigation, the chemical and structural properties of individual Ti 3 C 2 MXene sheets with associated surface groups are investigated at the atomic level by aberration corrected STEM-EELS. The MXene sheets are shown to exhibit a non-uniform coverage of O-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
308
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 463 publications
(331 citation statements)
references
References 29 publications
(70 reference statements)
13
308
1
1
Order By: Relevance
“…1b alone, 75% of each surface is covered by Nb adatoms and it is proposed that these are Nb adatoms that were adsorbed on the Nb 2 CT x surfaces during the applied etching, by complete or partial disintegration of adjacent MXene sheets. In strong contrast to other observations of MXenes, [34][35][36] the present example includes extensive amounts of adatoms. A high adsorption capacity of heavy metal adatoms on MXene surfaces was predicted by theoretical means (e.g.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…1b alone, 75% of each surface is covered by Nb adatoms and it is proposed that these are Nb adatoms that were adsorbed on the Nb 2 CT x surfaces during the applied etching, by complete or partial disintegration of adjacent MXene sheets. In strong contrast to other observations of MXenes, [34][35][36] the present example includes extensive amounts of adatoms. A high adsorption capacity of heavy metal adatoms on MXene surfaces was predicted by theoretical means (e.g.…”
contrasting
confidence: 99%
“…STEM has previously been successfully implemented for atomic level investigation of MXenes. [34][35][36] The present study reports on the presence and coordination of Nb 2 C surface adsorbed species, and their influence on the structural stability over time. The results were acquired using atomically resolved STEM imaging combined with EELS and STEM image simulations.…”
Section: Introductionmentioning
confidence: 94%
“…The flake stacking and surface terminations of various MXenes were studied recently by electron energy‐loss spectroscopy in transmission electron microscopy (TEM), neutron scattering, and nuclear magnetic resonance (NMR) spectroscopy . These studies confirmed that there is a random distribution of MXene surface terminations, rather than having a specific type of functionalities in one region .…”
Section: Properties Of Mxenesmentioning
confidence: 90%
“…[13c] Naguib et al proposed the first structural model of stacked Ti 3 C 2 (OH) 2 MXene via a density functional theory (DFT) simulation. [47] Meanwhile, Wang et al reported that the top sites of the Ti (c) atoms and the carbon atoms of the MXene monolayer are the most favorable locations for the functional groups and the intercalated sodium ions, respectively. A more precise DFT model and the ground state of multilayer Ti 3 C 2 (OH) 2 MXene have been discovered later by Mochalin and co-workers.…”
Section: Structural Properties and Surface Terminationsmentioning
confidence: 99%